Allergoid–mannan conjugates reprogram monocytes into tolerogenic dendritic cells via epigenetic and metabolic rewiring - Benito-Villalvilla, Cristina; Pérez-Diego, Mario; Angelina, Alba; Kisand, Kai; Rebane, Ana; Subiza, José Luis; Palomares, Oscar (Journal of allergy and clinical immunology, 2022)
Allergoid–mannan conjugates are novel vaccines for allergen-specific immunotherapy being currently assayed in phase 2 clinical trials. Allergoid–mannan conjugates target dendritic cells (DCs) and generate functional forkhead box P3 (FOXP3)-positive Treg cells, but their capacity to reprogram monocyte differentiation remains unknown. We studied whether allergoid–mannan conjugates could reprogram monocyte differentiation into tolerogenic DCs and the underlying molecular mechanisms. Monocytes from nonatopic and allergic subjects were differentiated into DCs under conventional protocols in the absence or presence of allergoid–mannan conjugates. ELISA, real-time quantitative PCR, coculture, flow cytometry, and suppression assay were performed. Metabolic and epigenetic techniques were also used. Monocyte differentiation from nonatopic and allergic subjects into DCs in the presence of allergoid–mannan conjugates yields stable tolerogenic DCs. Lipopolysaccharide-stimulated mannan-tolDCs show a significantly lower cytokine production, lower TNF-α/IL-10 ratio, and higher expression of the tolerogenic molecules PDL1, IDO, SOCS1, SOCS3, and IL10; and they induce higher numbers of functional FOXP3+ Treg cells than conventional DC counterparts. Mannan-tolDCs shift glucose metabolism from Warburg effect and lactate production to mitochondrial oxidative phosphorylation. They also display epigenetic reprogramming involving specific histone marks within tolerogenic loci and lower expression levels of histone deacetylase genes. Mannan-tolDCs significantly increase the expression of the anti-inflammatory miRNA-146a/b and decrease proinflammatory miRNA-155. Allergoid–mannan conjugates reprogram monocyte differentiation into stable tolerogenic DCs via epigenetic and metabolic reprogramming. Our findings shed light on the novel mechanisms by which allergoid–mannan conjugates might contribute to allergen tolerance induction during allergen-specific immunotherapy. [Display omitted]